AN ANALYSIS OF TYPES OF SPEECH ACTS IN WHIPLASH BY DAMIEN CHAZELLE - Immawan Iqbal Prasadana; Luwandi Suhartono; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research entitled “An Analysis of Types of Speech Acts in Whiplash by Damien Chazelle” was done in order to find out speech acts in the movie “Whiplash” and their functions. This research is in qualitative form and used descriptive method. The source of the data was the dialogue transcript of the movie. “Whiplash” was a one hour and forty minutes movie written and directed by Damien Chazelle. It is about Andrew Neiman, a student wanting to become a great jazz drummer faced with a killer teacher, Terrence Fletcher. The data was in form of words, phrases and sentences uttered by the main characters, being Andrew and Fletcher. The technique is content analysis. The context of each data was explained using S.P.E.A.K.I.N.G. technique and given after describing the speech acts. After the analysis, it was found that there are speech acts such as declarations, representatives, expressive, directives, and commissive. Declaration was uttered 7 times, representatives 30 times, expressive 27 times, directives, being the highest, 125 times, and commissive 6 times. Hopefully the result of this research can be useful for the readers. For students, hopefully, this research can be used as references for next research with different aspects. Keywords: Analysis, Speech Act, Whiplash